Методи і засоби ультразвукового контролю металовиробів трубчатого, стрижневого та пластинчатого типу (огляд ч. 1) - Плєснецов, Сергій Юрійович (НТУ "ХПІ", 2017)
Розглянуті основні засоби для проведення контролю металовиробів ультразвуковими та електромагніто-акустичними засобами. Серед контрольованих виробів присутні стрижнеподібні, трубчаті, пластинчаті та інші вироби, які виготовляються наи вітчизняних та зарубіжних підприємствах, як нові, так і ті, що знаходяться в експлуатації. Описані переваги та недоліки методів, їх вплив на продуктивність та якість оцінювання стану продукції, виявлення дефектів. Охарактеризовано типи коліивань, що використоваються у наведених методах, та їх вплив на кінцевий результат тестування. Розглянуто взаємовплив матеріалів та ультразвукових коливань, а також вплив матеріалів на кінцеві результати контролю.

The basic means for control of metal products by ultrasonic and electromagnetic acoustic means are considered. Among the controlled products, there are pivot, tubular, plate and other products that are manufactured at domestic and foreign enterprises, both new and in service. The advantages and disadvantages of the methods, their influence on productivity and quality of the estimation of the state of products, defects detection are described. The types of bumps used in the above methods and their influence on the final result of testing are described. The mutual influence of materials and ultrasonic vibrations, as well as the influence of materials on the final results of control are considered. Contact and non-contact ultrasonic electromagnetic-acoustic transducers are considered. Physical principles of electromagnetic-acoustic transduction are provided. Mathematical equations for evaluation of physical parameters required for sample testing are provided. Theoretical and experimental cocepts and prototype schematics for non-contact electromagneric-acoustic ultrasonic experimental transducer are given. Results of experimental evaluation of electromagnetic-acoustic prototype transducer are gven. Calculative schemes for methodology of developed electromagnetic-acoustic transducer are provided. Effectiveness of non-conact transducers of electromagnetic-acoustic type for testing of tubular, plate and rod-type samples is evaluated and considered superior to contact-type transducers.
Methods and means of ultrasonic control of metal products of tubular, rod and plate type (Review p. 1)
Keywords: трубчастий вироб; контроль електромагнітно-акустичний; хвиля; коливання; ЕМА; об’єкт контролю; ОК; п’єзоелектричний перетворювач; ПЕП; tubular product; electromagnetic acoustic control; wave; oscillations